2019
DOI: 10.1111/acel.13019
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized effects of aging on group 2 innate lymphoid cell development and function

Abstract: The effects of aging on innate immunity and the resulting impacts on immunosenescence remain poorly understood. Here, we report that aging induces compartmentalized changes to the development and function of group 2 innate lymphoid cells (ILC2), an ILC subset implicated in pulmonary homeostasis and tissue repair. Aging enhances bone marrow early ILC2 development through Notch signaling, but the newly generated circulating ILC2 are unable to settle in the lungs to replenish the concomitantly declining mature lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…This suggests that the innate immunity of ILC2s is not only limited to certain tissues, but also influences and interacts with different organs. According to a previous study, aging influences innate immunity ( 53 ). ILC2s in elderly lungs are not uniform in transcription and function, and cannot produce cytokines during influenza infection and homeostasis in vivo ( 53 ).…”
Section: Ilc2smentioning
confidence: 99%
“…This suggests that the innate immunity of ILC2s is not only limited to certain tissues, but also influences and interacts with different organs. According to a previous study, aging influences innate immunity ( 53 ). ILC2s in elderly lungs are not uniform in transcription and function, and cannot produce cytokines during influenza infection and homeostasis in vivo ( 53 ).…”
Section: Ilc2smentioning
confidence: 99%
“…As outlined previously, microbiota composition and function dramatically changes in aging individuals. 148 This by itself may already alter ILC function, although one could also imagine that altered ILC activity with age 149,150 can impact the composition of the commensal microbiota through various mechanisms that we have reviewed above. Several studies have reported that both dysbiosis and altered ILC functionality can be involved in tumorigenesis and also in the anti-tumour immune response.…”
Section: Microbiota à Ilcs Cancer and Agingmentioning
confidence: 99%
“…All mice were on the C57BL/6J genetic background. Adult (8-12 weeks old) and old (18)(19)(20)(21)(22)(23)(24) months old) mice were obtained from Jackson Labs or the National Institute on Aging (NIA) Aged Rodent Colony, and comparisons were made between groups of mice from the same vendor. Red5 mice were purchased from Jackson Labs (stock #030926) and were originally generated and described by Nussbaum et al (44).…”
Section: Materials and Methods Micementioning
confidence: 99%
“…We were especially intrigued by the loss of ILC2 in aged visceral adipose tissue because of their important role in promoting metabolic health and cold tolerance (17)(18)(19), both of which are impaired during aging. ILC2 exhibit strong tissue specificity (20) and are uniquely regulated in different tissues during the aging process (21)(22)(23), indicating that specific regulatory mechanisms might be responsible for their depletion in aged adipose tissue.…”
mentioning
confidence: 99%